Diminazene aceturate modified nanocomposite for improved efficacy in acute trypanosome infection - Oluwatosin Kudirat Shittu; Shaba Yisa Aaron; Mariam Damilola Oladuntoye; Bashir Lawal (Journal of Acute Disease, 2018)
Objective: To investigate the improved antitrypanocidal activity and toxicity of diminazene aceturate modified Nano drug in experimental rats.Methods: Aqueous leaf extract of Hyptis suaveolens was used to reduce gold tetrachloride to its nanoparticle size and this was characterized and formulates with naturally synthesized polyhydroxybutyrateas a Nano carrier. A total of thirty [30] albino rats were group into 6 (A-F) of 5 rats each & infected intraperitoneally with 0.2 mL of the inoculum containing about 1x103 Trypanosoma brucei brucei parasites per 0.2 mL of blood. Groups A and B were treated with 3 and 6 minutes released orange PHB, Groups C and D were treated with 15 and 30 minutes released mango PHB formulated tablet while Groups E and F were negative (untreated) and standard drug (Dininazene aceturare) respectively.Results: The free drug and modified orange synthesized polyhydroxy butyrate shows antitrypanocidal activities by reducing the replicating rate of the parasite as compared to infect untreated. While the modified- mango synthesized shows increasing order of replication. There were significant increases in all the haematological parameter evaluated in the infected treated groups compared to infect untreated. But no significant difference (P<0.05) observed in the Catalase activity in the serum and liver of all the groups whereas, the modified orange synthesized shows significant decrease in other enzymes activities evaluated when compared with the free drug, mango synthesized and the infected untreated groups.Conclusion: Orange synthesized modified diminazene aceturate show efficacy as free drug with limited toxicity that can enhance the therapeutic.